SUCCESSIVE – DIFFERENTIAL

1. 2. 3. 4. If y = f(x) then f (n) ( x ) is denoted by
dn y dx n
dn y dx n

or Dn y or y (n) or yn.

=

d ⎧ d n−1y ⎫ ⎪ ⎪ ⎨ ⎬. dx ⎪ dx n−1 ⎪ ⎩ ⎭

If y = (ax + b)m, then yn = m(m – 1)(m – 2) …… (m – n+1) (ax + b)m–n an. If f(x) = (ax + b)m, m ∈ Z, m >0, n ∈ N then (i) m < n ⇒ f (n) ( x ) = 0 (ii) m = n ⇒ f (n) ( x ) = n! an (iii) m > n ⇒ f (n) ( x ) =
m! (ax + b) m−n a n . (m − n)!

5. 6. 7. 8. 9. 10. 11.

If f(x) is a polynomial function of degree less than n where n ∈ N, the f (n) ( x ) = 0. If y =
( −1) n n! a n 1 , then yn = ax + b (ax + b) n +1 ( −1) n −1 (n − 1)! a n (ax + b) n

If y = log |ax + b| then yn =

.

If y = sin (ax + b), then yn = an sin (ax + b + nπ/2). If y = cos (ax + b), then yn = an cos (ax + b + nπ/2). If y = e ax +b , then yn = a n e ax +b If y = a bx +c , then yn = b n a bx + c (log a) n .

12. If y = eax sin (bx + c), then yn = rn eax sin (bx+c+nθ) where a = r cos θ, b = r sin θ. Now r = a 2 + b 2 , θ = tan −1 (b / a) . 13. If y = eax cos (bx + c), then yn = rn eax cos(bx+c+nθ) where a = r cos θ, b = r sin θ. Now r = a 2 + b 2 , θ = tan −1 (b / a) . 14. Leibnitz’s theorem : If f, g are two functions in x having nth derivatives then
( fg)(n) ( x ) = n C 0 f (n ) ( x )g( x ) + n C1f (n −1) ( x )g1( x ) +
n

C 2 f (n − 2 ) ( x )g( 2 ) ( x ) + ... + n Cr f (n − r ) ( x )g(r ) ( x ) + ... + n Cn f ( x )g(n ) ( x ) . C 0un v + n C1un −1v 1 + n C 2un − 2 v 2 + ... + n Cnuv n = C 0u1v n −1 + n C1u1v n −1 + n C 2u 2 v n − 2 + ... + n Cnun v.

15. If u, v are two functions in x, then (u, v)n =
n
n

1